User-Oriented Transformability of Interiors within the Framework of Changing Living Needs with the Covid-19 (Journal of Interior Design and Academy, 2022)
Space is a productive member of the change, distinction and to give a form. It is an organic, lively and changeable thing which is a kind of “transformable” dynamic phenomenon in its essence with the user. Developments and transformations in technology, together with the factors affecting these processes, activate the concept of "change" and redefine the phenomenon of "space" within the framework of time, space and life interaction. The COVID-19 epidemic, which emerged by the end of 2019 and affected the whole world also include our country in the first quarter of 2020, transformed both social life, daily life habbits, standarts and the use of built environment in an unprecedented way. In this study, it is aimed to determine the effects of the current conditions on the social habits of the person and the use of space. This information will be supported by literature research and it will be examined in terms of how the design can be handled in order to reach a "flexible" and livable spatial installation that can respond effectively to "instantaneous" needs. In addition, one of the other objectives is providing insights for effective use in spaces within the concepts of flexibility and technology for "spatial transformations" in the use of space in unpredictable situations.
Keywords: Interior space installaion; flexibility in use; technology; spatial transformation; COVID-19